Beginning Visual Studio LightSwitch development - Novák, István 1968- (Wiley Pub., 2011)
Learn how LightSwitch can accelerate and simplify application development As Microsoft's newest offering for simplifying application development, LightSwitch opens the development door to creating applications without writing code. This introductory, full-color book shows you how to quickly create, modify, and distribute information for your business with LightSwitch. Packed with simple example programs, this beginner-level resource guides you through a complete small business application using LightSwitch to demonstrate the capabilities of this exciting new tool. You'll explore the most commo.
Print version record
Keywords: Microsoft Visual studio; Web site development; Microsoft Visual studio LightSwitch; Sites Web; Développement; COMPUTERS; Programming; Open Source; COMPUTERS; Software Development & Engineering; General; COMPUTERS; Software Development & Engineering; Tools; Electrical & Computer Engineering; Engineering & Applied Sciences; Telecommunications; Computer Science